2008
DOI: 10.3200/jach.57.3.273-280
|View full text |Cite
|
Sign up to set email alerts
|

Willingness Among College Students to Help a Smoker Quit

Abstract: A high percentage of college students are willing to help a smoker. Future studies are needed to engage college students who are nonsmokers in tobacco control efforts, including the Healthy Campus 2010 initiatives to reduce smoking among college students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
(25 reference statements)
0
5
1
Order By: Relevance
“…Instead, we wanted to explore whether smoking status was related to willingness to help. However, in our sample we found no significant differences by smoking status, whereas in prior research we have found that non‐smokers were most likely willing to help 18.…”
Section: Discussioncontrasting
confidence: 99%
“…Instead, we wanted to explore whether smoking status was related to willingness to help. However, in our sample we found no significant differences by smoking status, whereas in prior research we have found that non‐smokers were most likely willing to help 18.…”
Section: Discussioncontrasting
confidence: 99%
“…The Cochrane review 2013, Tobacco Cessation Interventions for young people indicate similar data in the UK with 25% of [11][12][13][14][15] year olds having tried smoking at least once in 2011 compared with 53% in 1982 [24]. Five precent of this group of UK 11 -15 year olds were smoking regularly (>1 cigarettes/week) compared with 11% in 2001.…”
Section: Epidemiology Of Smoking In Adolescentsmentioning
confidence: 59%
“…Amongst occasional smokers followed over the next 6 years, parents' and peers' smoking predicted greater likelihood of escalation to daily smoking, whereas parental use of positive family management predicted a lower likelihood of escalation. Peers can also be very effective in supporting quit attempts, particularly if they are non-smokers [11]. Similarly, parental smoking predicts smoking initiation (more so if both parents smoke).…”
Section: Peer and Parental Effectsmentioning
confidence: 98%
“…and a 7-point Likert-type scale (for descriptive statistics, see Table 3). Single item measures of helping attitudes have demonstrated validity in previous studies (Bennett & Flores, 1998;Otten, Penner, & Altabe, 1991;Thomas et al, 2008), and we conducted a sensitivity analysis to be sure our conclusions would not be Contact. We indexed total contact (Dixon, Durrheim, & Tredoux, 2005) using a composite of two items that measured experience with individuals who abused substances.…”
Section: Instrumentsmentioning
confidence: 99%